2012
DOI: 10.1116/1.4765047
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties of as deposited and annealed ZrO2 influenced by atomic layer deposition, substrate, and doping

Abstract: Thin ZrO2 films are of high interest as high-k material in dynamic random access memory (DRAM), embedded dynamic random access memory, and resistive random access memory as well as for gate oxides. Actually, ZrO2 is predicted to be the key material in future DRAM generations below 20 nm. Profound knowledge of pure and doped ZrO2 thin films, especially of the structural properties, is essential in order to meet the requirements of future devices. This paper gives a detailed overview about the structural propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 30 publications
(32 reference statements)
5
22
0
Order By: Relevance
“…A depletion region (low capacitance state) in the negative voltage range and an accumulation region (high capacitance state) in the positive voltage range were clearly observed for MOS capacitors with either H 2 O or O 3 as oxidizer. The capacitance density went up gradually as the annealing temperature increased, which can be attributed to the improved crystalline quality of ZrO 2 films [ 17 ]. However, the MOS capacitors with H 2 O as the oxidizer showed a higher capacitance than that with O 3 oxidant.…”
Section: Resultsmentioning
confidence: 99%
“…A depletion region (low capacitance state) in the negative voltage range and an accumulation region (high capacitance state) in the positive voltage range were clearly observed for MOS capacitors with either H 2 O or O 3 as oxidizer. The capacitance density went up gradually as the annealing temperature increased, which can be attributed to the improved crystalline quality of ZrO 2 films [ 17 ]. However, the MOS capacitors with H 2 O as the oxidizer showed a higher capacitance than that with O 3 oxidant.…”
Section: Resultsmentioning
confidence: 99%
“…Since the crystallization temperature of ZrO 2 is significantly lower than that of HfO 2 [10,31,32], the ZrO 2 top layer crystallized before the sandwiched HfO 2 layer during annealing. Moreover, there is a large difference in the thermal expansion coefficients of thin film ZrO 2 and Si (10.3 and 2.5 10 À6 /K, respectively) [33]. These physical property differences would cause the sandwiched HfO 2 layer in the bilayer thin films to experience large thermal stresses during crystallization and subsequent cooling, and as a result, undergo phase transformation to the high pressure O-III phase.…”
Section: Zro 2 /Hfo 2 Bilayer Thin Filmsmentioning
confidence: 99%
“…Refractory metal capping, such as TiN, is well known to hinder the surface migration of atoms on the film surface. [2,11,[18][19][20][21][22][23] This work aims to demonstrate the capping layer effect by the TiN electrode on the HZO thin film, based on the phase transformation rate and the kinetic energy point of view, and underscores its importance when considering the origin of the ferroelectric o-phase in the HZO film. Nonetheless, a few reports experimentally showed that the grain size might not be the largest contributing factor to determine the final phase formation, [14,17] implying that there could be other potential factors, such as stress effect.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, a few reports experimentally showed that the grain size might not be the largest contributing factor to determine the final phase formation, implying that there could be other potential factors, such as stress effect. Combined effects of the electrode intermixing, such as Ti or N diffusion into the oxide layer from the TiN electrode, the lattice mismatch between the oxide layer and the electrode, and the thermal coefficient difference of the dielectric layer and the substrate upon annealing could engender mechanical confinement on the dielectric layer and influence the final phase formation …”
Section: Introductionmentioning
confidence: 99%